Effect of low pull headgear on head position - Santosh Kumar; Kalyana Chakravarthy Pentapati (Saudi Dental Journal)
Objective: To evaluate changes in head position following the use of low pull headgear (LHG) and compare these changes with an untreated control group. Subjects and methods: The test group comprised pre-treatment and post-treatment lateral cephalograms of 30 males, aged 11 ± 1.5 years, who were receiving LHG therapy for correction of Class II malocclusion. Pre-observation and post-observation lateral cephalograms of 25 untreated male subjects, aged 11 ± 1.6 years, served as controls. The average treatment time for the treatment group was 12 ± 2.02 months and the average observation period for the control group was 11 ± 1.03 months. Four postural variables (NSL/CVT, NSL/OPT, CVT/HOR, OPT/HOR) were measured to evaluate the head position in all subjects pre- and post-observations. Results: There was no significant difference in all the measurements concerning the head position within each group (p > 0.05). The mean differences of pre- and post-observations of 4 postural variables in the LHG group were 1.43, 0.9, −1.13, and −1.08, while those of the control group were 1.56, −0.32, −0.24, and 0.04, respectively. There was no significant difference between the headgear and control groups for any of the postural variables measured (p = 0.924, 0.338, 0.448, and 0.398, respectively). Conclusions: Although postural variables showed considerable variability in both groups, head position exhibited no significant changes over a period of 11–12 months either in the control or headgear group. Keywords: Craniofacial morphology, Growth, Headgear, Head position, Malocclusion